2020
DOI: 10.1080/00380768.2020.1843072
|View full text |Cite
|
Sign up to set email alerts
|

Microbial immobilization of ammonium and nitrate fertilizers induced by starch and cellulose in an agricultural soil

Abstract: Combined applications of plant residues and nitrogen (N) fertilizer in agroecosystems may increase N immobilization and reduce N loss through microbial propagation using fresh organic matter (FOM). However, the effects of different carbon (C) availabilities in FOM to microbes on the immobilization of two forms of fertilizer-N (NH 4 + -N and NO 3 − -N) are still not clear. In this study, starch (high availability) and cellulose (low availability) were used to represent different polysaccharides in crop residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…were found, confirming that MB is actively assimilating NH + 4 (Corre et al, 2003;Li et al, 2021;Ma et al, 2021). Serna-Chavez et al (2013) showed that MB can assimilate up to 138 mg N of 200 mg N added during a 3-day incubation.…”
Section: Nh4 Is the Main Process Of Global Gi But What Is Its Fate?mentioning
confidence: 55%
“…were found, confirming that MB is actively assimilating NH + 4 (Corre et al, 2003;Li et al, 2021;Ma et al, 2021). Serna-Chavez et al (2013) showed that MB can assimilate up to 138 mg N of 200 mg N added during a 3-day incubation.…”
Section: Nh4 Is the Main Process Of Global Gi But What Is Its Fate?mentioning
confidence: 55%
“…Sources of soil carbon (C) and OM such as crop residues (specifically corn stover in this study) has been widely promoted in agroecosystems all over the world to increase soil C stock, improving synchrony of nutrients supply ( e.g., from mineral fertilization) 44 46 . Therefore, keeping crop residues in the field could reduce the amount of N that leaches during the initial stage of crop growth when N demand is low, especially when there is high soil N leaching risk ( e.g., the snow melting or heavy spring rain events during early crop growth stages) 6 , 46 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Sources of soil carbon (C) and OM such as crop residues (specifically corn stover in this study) has been widely promoted in agroecosystems all over the world to increase soil C stock, improving synchrony of nutrients supply ( e.g., from mineral fertilization) 44 46 . Therefore, keeping crop residues in the field could reduce the amount of N that leaches during the initial stage of crop growth when N demand is low, especially when there is high soil N leaching risk ( e.g., the snow melting or heavy spring rain events during early crop growth stages) 6 , 46 49 . The subsequent remineralization of the immobilized N can supply mineral N for crop growth, indicating that the incorporation of corn stover, which contains a larger amount of C with high availability, can improve N synchrony to corn cropping systems by increasing NH 4 + availability.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the changes in DOC. Carbon availability can strongly in uence the N immobilization process (Ma et al 2020). Reduced availability of labile carbon leads to a decrease in microbial biomass carbon, thus weakening the microbial N immobilization process (Baldos et al 2015).…”
Section: Rice Genotypes Signi Cantly Affect Nitri Cation Rates In Rhi...mentioning
confidence: 99%